Branch, Group and Chain Banking/Rural Banking Reform (Book). - Wxidenhammer, Robert (The Accounting Review, 1932)
Reviews two books on banking. "Branch, Group and Chain Banking," by Gaines Thompson Cartinhour; "Rural Banking Reform," by Charles Wallace Collins.